Shunt Active and Series Active Filters-Based Power Quality Conditioner for Matrix Converter. (11th July 2011) - Paul, P. Jeno
Abstract : This paper proposes a series active filter and shunt active filter to minimize the power quality impact present in matrix converters instead of passive filter. A matrix converter produces significant harmonics and nonstandard frequency components into load. The proposed system compensates the sag and swell problems efficiently in matrix converter. The proposed system has been tested and validated on the matrix converter using MATLAB/Simulink software. Simulated results confirm that the active power filters can maintain high performance for matrix converter.